The effect of adding uphill treadmill exercise to standard therapy on dynamic balance function in patients with knee osteoarthritis at RSUD Dr. Soetomo in Surabaya - Pratitissari, Eka Dewi; Tinduh, Damayanti; Prawitri, Yudith Dian; Melaniani, Soenarnatalina (Edelweiss Applied Science and Technology, 2025)
Balance involves integrating sensory input and motor responses to maintain body position, while the "Timed Up and Go" test evaluates functional mobility quickly and effectively. The study aimed to determine the effect of adding uphill treadmill exercise to standard therapy on dynamic balance function in patients with knee osteoarthritis. The control group received standard therapy (TENS and Q-bench), while the treatment group also performed uphill treadmill exercise (8° incline, 1.1 m/s, 30 minutes, twice weekly for 5 weeks). Dynamic balance was assessed using the "Timed Up and Go" test. Measurements were taken three times: at the beginning of the study (1 day before exercise), at the end of the study (1 day after the last exercise), and 20 days after the last exercise. The treatment group demonstrated significant improvements in TUG scores compared to the control group at T1 (p = 0.01, Cohen’s D = 1.22) and T2 (p < 0.01, Cohen’s D = 1.43). Participants aged 55–59, predominantly female and with Grade II knee OA, showed significant improvements in Timed Up and Go scores, particularly in the treatment group receiving uphill treadmill exercise alongside TENS and quadriceps strengthening, highlighting the efficacy of this combined approach in enhancing functional balance and mobility by targeting muscle strength and reducing stiffness. There was a better improvement in "Timed Up and Go" values in measurements after exercise and follow-up in Grade II-III knee osteoarthritis patients who received additional uphill treadmill exercise compared to standard therapy.